Role of interleukin-1β in nerve growth factor expression, neurogenesis and deep dyspareunia in endometriosis - Peng, Bo (Hum Reprod, 2020)
STUDY QUESTION: Does interleukin-1β (IL-1β) play a role in promoting nerve growth factor expression, neurogenesis and deep dyspareunia in endometriosis? SUMMARY ANSWER: IL-1β directly stimulates nerve growth factor (NGF) expression in endometriosis and is associated with local neurogenesis around endometriosis and more severe deep dyspareunia. WHAT IS KNOWN ALREADY: Local nerve density around endometriosis (using the pan-neuronal marker PGP9.5) is associated with deep dyspareunia in endometriosis, mediated in part by NGF expression. STUDY DESIGN, SIZE, DURATION: This in vitro study included endometriotic tissue samples from 45 patients. PARTICIPANTS/MATERIALS, SETTING, METHODS: This study was conducted in a university hospital affiliated research institute and included 45 women with surgically excised deep uterosacral/rectovaginal endometriosis (DIE, n = 12), ovarian endometriomas (OMA, n = 14) or superficial peritoneal uterosacral/cul-de-sac endometriosis (SUP, n = 19). Immunolocalisation of IL-1β, IL-1 receptor type 1 (IL-1R1), NGF and PGP9.5 in endometriotic tissues was examined by immunohistochemistry (IHC), and the intensity of IHC staining in the endometriotic epithelium and stroma was semi-quantitatively evaluated using the Histoscore method (H-score). For each case, deep dyspareunia was pre-operatively rated by the patient on an 11-point numeric rating scale (0–10). In addition, primary endometriosis stromal cells were isolated and cultured from surgically excised endometriosis. These cells were treated with IL-1β alone or in combination of Anakinra (an inhibitor of IL-1R1), small inference RNA (siRNA) against IL-1R1, siRNA against c-FOS or NGF neutralising antibody. The mRNA and protein levels of target genes (NGF and c-FOS) were assessed by reverse-transcription qPCR and western blot/ELISA, respectively. Furthermore, immunofluorescent microscopy was used to examine the neurite growth of rat pheochromocytoma PC-12 cells, as an in vitro model of neurogenesis. MAIN RESULTS AND THE ROLE OF CHANCE: For IHC, IL-1β expression in the endometriosis epithelium was significantly associated with more severe deep dyspareunia (r = 0.37, P = 0.02), higher nerve fibre bundle density around endometriosis (r = 0.42, P = 0.01) and greater NGF expression by the endometriosis epithelium (r = 0.42, P = 0.01) and stroma (r = 0.45, P = 0.01). In primary endometriosis stromal cells, treatment with exogenous IL-1β significantly increased the mRNA and protein levels of NGF and c-FOS. Pre-treatment with Anakinra, siRNA against IL-1R1, or siRNA against c-FOS, each attenuated IL-1 β-induced increases of NGF expression. In addition, supernatants from IL-1β treated endometriosis stromal cells significantly stimulated PC-12 neurite growth compared to controls, and these effects could be attenuated by pre-treatment with NGF neutralising antibody or Anakinra. LARGE-SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: We did not have data from cultures of endometriosis glandular epithelium, due to the known difficulties with primary cultures of this cell type. WIDER IMPLICATIONS OF THE FINDINGS: Our study revealed a mechanism for deep dyspareunia in endometriosis, whereby IL-1β stimulates NGF expression, promoting local neurogenesis around endometriosis, which in turn leads to tender pelvic anatomic sites and thus deep-hitting dyspareunia. There may also be potential for drug targeting of IL-1β and/or NGF in the management of endometriosis-associated pain. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by grants from the Canadian Institutes of Health Research (MOP-142273 and PJT-156084). P.Y. is also supported by a Health Professional Investigator Award from the Michael Smith Foundation for Health Research. MB has financial affiliations with Abbvie and Allergan. Otherwise, there are no conflicts of interest to declare.